2021
DOI: 10.1371/journal.pone.0258418
|View full text |Cite
|
Sign up to set email alerts
|

Unequal geographic distribution of water and sanitation at the household and school level in Sudan

Abstract: The Sudanese Government launched the National SDG-6 Plan and commences its implementation to achieve and sustain universal and equitable access to basic WASH services by 2030. It is critical to understand the geographical heterogeneity of Sudan and patterns in the inequality of access to safe drinking water and sanitation. Through such research, the disease control strategy can be optimized, and resource allocation can be prioritized. We explored spatial heterogeneity and inequality in access to improved water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The past decade has witnessed significant progress in access to drinking water sources globally (Mosello, 2017). Despite these improvements, there are considerable disparities in access to and use of improved water 1 within cities of the developing world (Alba et al, 2020;Cha et al, 2021;Deshpande et al, 2020;Mutono et al, 2022). Since access to improved drinking water is a central concern for population health and well-being, several international organizations including the United Nations, the World Health Organization (WHO), and United Nations Children's Fund (UNICEF) have been very proactive in setting targets and providing support for universal access to safe drinking water.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The past decade has witnessed significant progress in access to drinking water sources globally (Mosello, 2017). Despite these improvements, there are considerable disparities in access to and use of improved water 1 within cities of the developing world (Alba et al, 2020;Cha et al, 2021;Deshpande et al, 2020;Mutono et al, 2022). Since access to improved drinking water is a central concern for population health and well-being, several international organizations including the United Nations, the World Health Organization (WHO), and United Nations Children's Fund (UNICEF) have been very proactive in setting targets and providing support for universal access to safe drinking water.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on variations in drinking water sources in SSA have largely focused on between-country analyses (Adams & Smiley, 2018;Armah et al, 2018;Deshpande et al, 2020;Hopewell & Graham, 2014;Pullan et al, 2014). A few studies have also examined disparities in drinking water within countries and major SSA cities (Cha et al, 2021;Cole et al, 2018;Grace et al, 2017;Osei et al, 2015;Songsore & McGranahan, 1998;Thompson et al, 2000). However, only a handful of studies have examined water drinking patterns at localized settings 2 for fast growing metropolitan cities in SSA (see Alba et al, 2019;Cha et al, 2021;Cole et al, 2018;Thompson et al, 2000), which is needed to better understand inequality in the provision of local infrastructure and essential services.…”
Section: Introductionmentioning
confidence: 99%
“…Primary education from age six for 8 years has been compulsory in Sudan since 1998 [17]. According to a nationwide survey conducted in 2017, the percentages of Sudanese households with improved water and sanitation were 86% and 16%, respectively [18]. It has been reported that about 10% of Sudanese live a nomadic life and that more than 30% depend on farming and animal husbandry.…”
Section: Study Areasmentioning
confidence: 99%
“…From January to February 2017, a nationwide schistosomiasis survey was conducted in Sudan in 1,711 randomly selected primary schools to estimate the statewide prevalence of Schistosoma haematobium and Schistosoma mansoni in the 18 states [6,7]. Random selection was chosen to obtain precise estimates of schistosomiasis prevalence and the number of infected individuals.…”
mentioning
confidence: 99%